The microhardness Property of the Biomedical commercially pure titanium-strontium oxide composite alloy after anodic oxidation - Soodad A. Muhammed1 • Aseel Mohammed Al-Khafaji 2.Haydar H. Jamal Al Deen3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
high level of corrosion resistance, a high strength to weight ratio, and bio-compatibility, titanium as well as its alloys are extremely valuable today because of its enchanted qualities. With the use of sulfuric acid as electrolyte in the electrochemical circuit, the formation of anodic films and variations in aesthetic appearance regarding anodized titanium titanium-strontium oxide composite alloy surface are examined in the work that is currently being presented. This article concentrates on the most recent advances of a novel, commercially pure titanium-strontium oxide composite alloy that has been anodized. With regard to biomedical applications, strontium oxide was added in a particular quantity (6%) by wt.%. With the use of microhardness testing device, the impact of strontium oxide additions and anodic oxidation were examined. The findings show that strontium oxide additions increase microhardness. Additionally, titanium alloys with 6 wt.% strontium oxide microparticle additions that have been anodized exhibit no difference than those that have not been anodized. The produced strontium oxide-cp titanium composite alloy offers significant potential for use as a biomaterial, particularly in dental applications, as evidenced by high wettability and increased roughness.Corresponding Author